Digital Freedom: How Much Can You Handle? - Batra, Narain D. (Rowman & Littlefield Publishers, 2007)
In Digital Freedom, N. D. Batra explores the tension between the boundlessness of the Internet and the boundaries of the marketplace, as well as the resulting impact on human expression, privacy, and social controls. Digital Freedom is an exploration of and meditation on the question: How much freedom does a person need? The question evokes Tolstoy's parable, 'How much land does a man need?' Is freedom an acquired taste, much like one's love for symphony orchestra? Or, is it a necessity? After all, civilizations in the past have produced monumental works in all fields of human endeavor without as much obsession with individual freedom as we have today. Digital Freedom explores these issues_including surveillance, intellectual property, and copyright_from the perspective of an evolutionary, self-organizing social system. This system both creates and assimilates innovations and, in the process, undergoes reorganization and renewal.